1989
DOI: 10.3379/jmsjmag.13.s1_43
|View full text |Cite
|
Sign up to set email alerts
|

Curvature of Perpendicular Magnetization Transitions Across Track

Abstract: The nature of the perpendicular recording process at track edges is of interest in the design of very high track density recording systems. Recording experiments carried out on a large-scale model exhibit across-track curvature of the recorded transitions of perpendicular magnetization. Calculations using a simple three-dimensional analytical recording model suggest that the curvature is associated with the across-track variation of the demagnetizing field produced by the recorded magnetization pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…By using the analytical model, characteristics of across-track curvature of perpendicular magnetization transitions have been studied. The head and medium geometry and magnetic properties used in this study are the same as for the large scale model described in the previous paper, [5] except for the head-to-back-layer spacing S and medium coercivity He. Thus, it was assumed that the main pole of the perpendicular recording head has thickness Tm = Imm and width W = 9.5mm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By using the analytical model, characteristics of across-track curvature of perpendicular magnetization transitions have been studied. The head and medium geometry and magnetic properties used in this study are the same as for the large scale model described in the previous paper, [5] except for the head-to-back-layer spacing S and medium coercivity He. Thus, it was assumed that the main pole of the perpendicular recording head has thickness Tm = Imm and width W = 9.5mm.…”
Section: Resultsmentioning
confidence: 99%
“…Since Iwasaki and Nakamura reported that the rapid drop of writing field at track edge in perpendicular recording compared with longitudinal recording [1], several examinations of narrow track perpendicular recording have been carried out experimentally [2] [3] and analytically [4]. Previously, we also reported that the across-track curvature of a recorded perpendicular transition was observed on a large scale recording model recording in contact and this result was predicted from a simple three-dimensional analytical recording model [5]. In this paper, further study on the phenomenon of recorded perpendicular transitions across-track using this analytical model is presented.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation